IMPLEMENTATION OF THE SEKOLAH RAKYAT PROGRAM IN SURABAYA CITY USING THE INTEGRATIVE CAPACITY FRAMEWORK APPROACH - Najwa Tsaniya Anjainah; Singgih Manggalou (SOSIOEDUKASI, 2026)
Poverty remains a major development challenge in Indonesia because it limits access to quality education. To break intergenerational poverty, the government launched the Sekolah Rakyat Program for children from extremely poor, poor, and vulnerable families. This study analyzes the implementation of the Sekolah Rakyat Program in Surabaya City using the Integrative Capacity Framework developed by Vince (2024). The study uses a descriptive qualitative method. Data were collected through interviews, observation, and documentation involving program managers, the Surabaya City Social Service, teachers, foster guardians, and students. Data analysis used data reduction, data display, and conclusion drawing. The findings indicate that the program has been implemented effectively across the main dimensions of the Integrative Capacity Framework. Policy coordination and institutional cohesion are demonstrated through collaboration among the central government, local government, educational institutions, and other stakeholders.Accountability and legitimacy are reflected in a clear legal framework and a structured student selection process, while resource capacity is supported by adequate educational and dormitory facilities despite the continued need for additional professional mentoring staff. Although institutional architecture provides clear role distribution, strengthening local institutional capacity remains necessary to ensure program sustainability. The study concludes that strengthening institutional and resource capacity is essential to maximize the program's contribution to expanding equitable educational access and supporting long-term poverty reduction policies.